Polymeric Fibers as Scaffolds for Spinal Cord Injury: A Systematic Review - Cheng, Yuanpei; Zhang, Yanbo; Wu, Han (Frontiers in Bioengineering and Biotechnology, 2022)
Spinal cord injury (SCI) is a complex neurological condition caused by trauma, inflammation, and other diseases, which often leads to permanent changes in strength and sensory function below the injured site. Changes in the microenvironment and secondary injuries continue to pose challenges for nerve repair and recovery after SCI. Recently, there has been progress in the treatment of SCI with the use of scaffolds for neural tissue engineering. Polymeric fibers fabricated by electrospinning etc. have been increasingly used in SCI therapy owing to their biocompatibility, complex porous structure, high porosity, and large specific surface area. Polymer fibers simulate natural extracellular matrix of the nerve fiber and guide axon growth. Moreover, multiple channels of polymer fiber simulate the bundle of nerves. Polymer fibers with porous structure can be used as carriers loaded with drugs, nerve growth factors and cells. As conductive fibers, polymer fibers have electrical stimulation of nerve function. This paper reviews the fabrication, characterization, and application in SCI therapy of polymeric fibers, as well as potential challenges and future perspectives regarding their application.